2013
DOI: 10.1007/s11999-013-3183-4
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Metal in Total Knee Arthroplasty Associated with Higher Knee Scores: A Randomized Controlled Trial

Abstract: Background Porous tantalum is an option of cementless fixation for TKA, but there is no randomized comparison with a cemented implant in a mid-term followup. Questions/purposes We asked whether a tibial component fixed by a porous tantalum system might achieve (1) better clinical outcome as reflected by the Knee Society Score (KSS) and WOMAC Osteoarthritis Index, (2) fewer complications and reoperations, and (3) improved radiographic results with respect to aseptic loosening compared with a conventional cement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 60 publications
1
52
0
Order By: Relevance
“…Highly porous metal tibias (both uncemented and cemented) were no different from traditional cemented modular tibial modular components in terms of survivorship at 5 years using a intention-to-treat analysis (96.8% [1]; 97.6% [2]; 96.7% [3]; p = 0.59). A per-protocol analysis revealed that no highly porous metal tibia was revised for aseptic loosening.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Highly porous metal tibias (both uncemented and cemented) were no different from traditional cemented modular tibial modular components in terms of survivorship at 5 years using a intention-to-treat analysis (96.8% [1]; 97.6% [2]; 96.7% [3]; p = 0.59). A per-protocol analysis revealed that no highly porous metal tibia was revised for aseptic loosening.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3. Clinical and radiographic results at the latest followup tibia or a traditional modular cemented tibia, FernandezFairen et al [3] found no difference in durability at 5 years. At a minimum 5 years followup, a prospective analysis of 100 patients aged \ 55 years with an uncemented trabecular metal tibia by Kamath et al [6] found 97% survival for all causes and 100% survival with aseptic loosening of the tibia as the endpoint.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Two-year outcome studies using radiostereometric analysis data have demonstrated excellent fixation with only mild subsidence among nonmodular trabecular metal tibial trays [7][8][9][10][11][12][13][14][15][16]. Recently, modular trabecular metal tibial components have become available for clinical use (Fig.…”
mentioning
confidence: 99%
“…The orthopedic literature currently includes several prospective, randomized series comparing cementless and cemented fixation at various follow-up intervals [7,[11][12][13][14][17][18][19][20][21]. Currently, there are no published studies evaluating modular trabecular metal tibial trays.…”
mentioning
confidence: 99%